Surfactant type affects the washing effect of cinnamon leaf essential oil emulsion on kale leaves. (15th January 2019) - Kang, Ji-Hoon; Park, Su-Jong; Park, Jun-Beom; Song, Kyung Bin
Highlights: Washing effects of CL-EO emulsions by surfactant type were compared. CL-EO emulsion with cetylpyridinium chloride (CLC) had the highest washing effect. CLC achieved higher log reductions than NaOCl treatment. CLC can be used as an alternative to chlorine for fresh-cut produce washing. Abstract: With increasing foodborne illness associated with fresh-cut produce, a chemical sanitizer to substitute chlorine is needed in the food industry. This study examined the washing effect of cinnamon leaf essential oil (CL-EO) emulsions on fresh-cut produce according to the ionic properties of surfactants. Washing effect of CL-EO emulsion (CLC) with cetylpyridinium chloride was the highest among all treatments on kale leaves. After CLC treatment, 1.83 and 1.54 log reductions against Listeria monocytogenes and Escherichia coli O157:H7 were achieved, respectively, compared to washing with distilled water, and had about 0.6 log-reductions higher than NaOCl treatment. CL-EO droplets in CLC had a positive ζ-potential (+55 mV) compared to other emulsions. These results indicate that ionic properties of surfactants are very important in the washing effect of CL-EO emulsion. Additionally, CLC treatment did not affect the quality of kale leaves during storage. Therefore, CLC can be an effective chemical sanitizer for washing kale leaves.